LncRNA growth arrest‐specific transcript 5 targets miR‐21 gene and regulates bladder cancer cell proliferation and apoptosis through PTEN - Dong Chen; Yihong Guo; Yaqiu Chen; Qiaonan Guo; Junyi Chen; Yining Li; Qiuping Zheng; Minyao Jiang; Ming Xi; Lu Cheng (Cancer Medicine)
Abstract The aim of this study was to investigate the mechanism by which growth arrest‐specific transcript 5 (GAS5) regulates bladder cancer cells. Bladder cancer samples were collected and tested for experiment. Dual‐luciferase reporter assay was used to verify the downstream target genes for GAS5 and miR‐21. The expression level of GAS5 was decreased and that of miR‐21 was increased, indicating a negative correlation between the two. Patients with high GAS5 level and low miR‐21 level had relatively longer survival rates. GAS5 inhibited bladder cancer cells proliferation and promoted apoptosis, and miR‐21 had the opposite effects. MiR‐21 was a direct target for GAS5, whereas phosphatase and tensin homolog (PTEN) was a direct target gene of miR‐21. Low expression of miR‐21 could reverse the proliferative and antiapoptotic effects caused by GAS5 silencing. High levels of GAS5 and low levels of miR‐21 might be associated with a higher survival rate in bladder cancer patients. GAS5 could exert antiproliferative and proapoptotic effects on bladder cancer cells through miR‐21 and PTEN.